Advances in culture, tourism and hospitality research. Vol. 2 - Woodside, Arch G. (Emerald, 2008)
This volume provides useful answers to the following questions: how do tourists go about seeking high novelty and yet return to the same destination year-after-year? How do some firms in the same industry end up embracing industrial tourism while other firms reject such business models? What simple and complex heuristics do freely-independent-travelers apply pre-trip and during the trip in deciding where to go and what to do? What metrics are useful for measuring the impact of activity-focused tourism on the well-being of regional areas? How do executive leadership styles affect employee satisfaction in international tourist hotels? What action and outcome metrics are useful for measuring performance management auditing and destination marketing organization planning and implementing?In terms of the first question, research on tourists' risk-handling behavior provides a useful framework for explaining their novelty seeking proneness. The first paper of the volume provides a complete research report on how tourists' risk-handling behavior explains contingencies in novelty seeking regarding repeat visits to a given destination. How executives process industrial tourism models depends on whether or not they view such enterprise development as a core or peripheral business. The second paper provides thick descriptions of alternative process approaches whilst the third reports a mixed-methods (interpretative and positivistic) research design to provide a thorough report on FITs' (fully independent travellers') pre-trip and trip thinking and doing behavior. This research approach shows how FITs take advantage of serendipitous opportunities to experience a number of locations, attractions, and activities that they had neither actively researched nor planned.The fourth paper applies the fields of travel research and community economic development (CED) within an ethnographic and survey research study on mural tourism which shows how tourism business models can be successful for nurturing CED. The following paper provides both evidence on how leadership styles affect the success of international hotel operations as well as templates on how to measure both leadership styles and subsequent impacts on hotel operations. The final paper includes a longitudinal case study of management performance audits of a government destination marketing organization (DMO) to illustrate the use of templates for measuring both auditor and DMO executives behavior and performance outcomes. As such, this paper concludes what is a diverse and engaging volume of Advances in Culture Tourism and Hospitality Research.
Keywords: Social Science -- Anthropology -- General.; Cultural studies.; Tourism industry.; Tourism.; Hospitality industry.; elektronické knihy; electronic books